Green Synthesis Of Tio2 – Ag Nanocomposites For Self-Cleaning And Antimicrobial Properties On Cotton Fabric - S. Muniandy, Sunderishwary (2018)
Green chemistry approach is an emerging interdisciplinary area that is expected to have wide ranging implications in all fields of science and technology. Although green chemistry is still in its infancy, it is already proving to be a useful tool in improving the performance of nanomaterial and generating worldwide interest. Titanium (IV) dioxide nanoparticles (TiO2 NPs), silver nanoparticles (AgNPs) and titanium dioxide – silver nanocomposites (TiO2 – NCs) have been successfully synthesised using hydrothermal green chemistry approaches.